Anthelmintic resistance against benzimidazoles and macrocyclic lactones in strongyle populations on cattle farms in northern Germany - Paula Ehnert; Jürgen Krücken; Stefan Fiedler; Fabian Horn; Christina S. Helm; Ann Neubert; Wiebke Weiher; Werner Terhalle; Stephan Steuber; Ricarda Daher; Georg von Samson-Himmelstjerna (Scientific Reports)
Abstract Anthelmintic resistance (AR) in cattle gastrointestinal nematodes (GIN) is an increasing global concern, with low to moderate levels recently documented in Central Europe. This study reports on resistance against both macrocyclic lactones (MLs) and benzimidazoles (BZs) in northern Germany, highlighting that AR is spreading. The fecal egg count reduction test (FECRT) remains the primary tool for AR assessment, yet differing methodologies and recent guideline updates complicate resistance interpretation across studies. Statistical methods, such as Bayesian approaches used by eggCounts and bayescount, yield varying confidence intervals, further influencing results. Notably, the nemabiome analysis identified Ostertagia ostertagi and Cooperia oncophora as predominant species in the region, though unexpected diversity among farms with additional GIN species occurring sometimes even at high frequency, suggests morphological analysis of coprocultures may underestimate species prevalence. Detecting AR against both drug classes on some farms underscores the urgency of implementing sustainable strategies, such as targeted selective treatment and combinations of anthelmintics with different mode of action, to prevent scenarios of multi-drug resistance observed elsewhere. Effective resistance management requires immediate discussions with veterinarians and stakeholders to steer toward informed, preventive measures in cattle farming.